The origins and evolution of Islamic law - Hallaq, Wael B. (Themes in Islamic law ;, 2005)
The book explores the interplay between law and politics, demonstrating how the jurists and ruling elite led a symbiotic existence that paradoxically allowed Islamic law to become uniquely independent of the "state."